(untitled) (Academia Journal of Medicine, 2025)
Mutrashmari, commonly known as renal calculi or kidney stones, is a significant health concern characterized by the formation of stones in the urinary tract. Ayurveda classifies it as one of the Ashtamahagada due to its complexity and challenges in treatment. It arises from an imbalance in Vata, Pitta, and Kapha doshas and is influenced by factors such as improper diet, sedentary lifestyle, dehydration, excessive calcium intake, metabolic disorders, and genetic predisposition. Clinically, it presents with severe pain, dysuria, oliguria, hematuria, nausea, and vomiting. This case study evaluates the impact of Ayurvedic management in a 34-year-old male diagnosed with Mutrashmari at Jeena Sikho Lifecare Limited Hospital, Hyderabad, Telangana, India. Following two months of Ayurvedic treatment, a comparative USG revealed a reduction in stone size, with the right kidney calculus decreasing from 4.6 mm to 2 mm and the left kidney calculus reducing from 3.7 mm to 2.7 mm. The patient experienced significant symptomatic relief, including reduced pain and improved urine output. These findings support the efficacy of Ayurvedic interventions in renal calculus management. However, further clinical trials are required to validate these results and establish standardized treatment protocols.